Beyond Philanthropy: A Critical Accounting Policy Brief on Lembaga Dana Umat and the Politics of Redistribution - Prabowo, Muhammad Aras; Kasdi, Abdurrohman (ZISWAF, 2026)
The emergence of Lembaga Dana Umat (LDU) has generated significant debate regarding the governance, accountability, and redistribution of religious social finance in Indonesia. Existing studies predominantly interpret religious funds through a philanthropic perspective, providing limited explanation of their broader institutional and political implications. This study aims to develop a critical understanding of LDU as a redistributive accounting institution by integrating Critical Perspectives on Accounting (CPA), Islamic social finance, and governance literature. Employing a qualitative conceptual approach based on systematic literature synthesis and multiparadigmatic analysis, the study examines how accounting practices influence the legitimacy, allocation, and public accountability of religious funds. The findings reveal three key issues. First, conventional accountability emphasizes financial collection and distribution while neglecting distributive justice and structural inequality. Second, LDU operates as a political-accounting institution that shapes beneficiary classification, public value creation, and redistributive governance. Third, a critical Islamic and interfaith accounting framework provides a more comprehensive model by integrating financial stewardship, ethical responsibility, social justice, and democratic accountability. This study contributes to the development of CPA by extending critical accounting analysis to faith-based social finance and proposes a policy framework emphasizing independent oversight, participatory governance, differentiated fund management, and regulatory alignment to strengthen redistributive accountability in pluralistic societies.